El papel de España en la política africana de Marcello Caetano - Tíscar Santiago, María José (Espacio Tiempo y Forma. Serie V, Historia Contemporánea, 2007)
Apoyo mutuo en la vida internacional y cooperación en el terreno bilateral son los dos principios, ya fijados en la etapa anterior, que sustentan las relaciones luso-españolas durante el marcelismo. El primero comprende tres tipos de ayuda por parte de España: contención de las condenas a Portugal en las organizaciones internacionales; apoyo a las necesidades de armamento del Ejército portugués en África aprovechando los nexos derivados del Pacto Ibérico y asunción de la representación de los intereses portugueses en aquellos países africanos que, siguiendo las consignas de la OUA, rompen relaciones diplomáticas con Portugal. En el ámbito bilateral es donde se rompe la tónica anterior pues los tecnócratas españoles, que ahora alcanzan Asuntos Exteriores, pretenden rentabilizar los servicios prestados en el ámbito multilateral para iniciar vías de expansión en el mercado portugués. Mutual support in international affairs and bilateral cooperation were two of the principles, which having been established during the previous phase, sustained Lusitanian-Spanish relations during Marcelism. The former consisted of three types of Spanish support: restraint in Spain’s condemnation of Portugal in international organisations; support of the Portuguese army in Africa in their need for arms, via the exploitation of links forged in the Iberian Pact; and the assumption of the representation of Portuguese interests in those African countries which, having followed the recommendations of the Organization of African Unity (OAU), had broken diplomatic relations with Portugal. It is in bilateral relations where the previous tendency changed, as the Spanish technocrats who had now reached the Foreign Office, wanted to capitalise services rendered in multilateral relations, to initiate an expansion in the Portuguese market. Iberian relations were especially intense in African states where forced diplomatic coexistence gave them a very different air to that maintained in other areas.